Refinement of in vivo optical imaging: Development of a real-time respiration monitoring system. (October 2018) - Gomes, Ana L; Gilchrist, Stuart; Kersemans, Veerle; Westcott, Marcus; Smart, Sean
In vivo optical imaging enables detection and quantification of light-emitting compounds from the whole body in small animals such as the mouse, but it typically requires the use of anaesthetics for subject immobilisation due to long exposure times. Excessively deep anaesthesia can result in unacceptably compromised physiology, whilst excessively light anaesthesia can result in animals waking up. Here we report a respiratory monitoring setup for an in vivo bioluminescence and fluorescence imaging device which simultaneously allows real-time adaptive control of anaesthesia depth in multiple animals to (i) potentially increase the consistency between animals, (ii) ensure animals are maintained within minimally intrusive, adequate anaesthetic plane and (iii) provide a valuable refinement strategy for a common challenge within animal-based research.